2017
DOI: 10.1002/oby.21815
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Low‐Grade Inflammation Following Long‐Term Dietary Intervention in Postmenopausal Women with Obesity

Abstract: A reduction of abdominal obesity in postmenopausal women is linked to specific changes in inflammation-related adipose gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(53 citation statements)
references
References 41 publications
2
51
0
Order By: Relevance
“… Estimated food records during 4 days at baseline, 6 months and 24 months. Blomquist C, et al 2018 [ 44 ] Centesimal composition: Not informed. Included: lean meat, fish, eggs, vegetables, fruits, nuts, avocado, rapeseed oil and olive oil.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Estimated food records during 4 days at baseline, 6 months and 24 months. Blomquist C, et al 2018 [ 44 ] Centesimal composition: Not informed. Included: lean meat, fish, eggs, vegetables, fruits, nuts, avocado, rapeseed oil and olive oil.…”
Section: Resultsmentioning
confidence: 99%
“…The three markers were evaluated in five studies [ 23 , 26 , 27 , 30 , 37 ]; weight and WC were evaluated in three studies [ 40 , 41 , 44 ], and weight only was evaluated in three other studies [ 14 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study selection: The electronic search on literature yielded 2722 titles, of which 26 were reviewed in full text considering the criteria of eligibility. Of these studies, 19 papers were excluded for the following reasons: 1) seven studies reported no data related to our target outcomes (Baumgartner et al, 2009, Frassetto et al, 2013, Genoni et al, 2016a, Jonsson et al, 2010, Jonsson et al, 2013, Lee et al, 2017, Singh et al, 2012; 2) six studies reported duplicated results (Andersson et al, 2016, Blomquist et al, 2017a, Blomquist et al, 2017b, Boraxbekk et al, 2015, Sandberg et al, 2012, Stomby et al, 2015; 3) four studies had single-arm design with no control group (Frassetto et al, 2009, Osterdahl et al, 2008, Ryberg et al, 2013, Trexler et al, 2013; 4) one study evaluated the effect of PD along with exercise (Otten et al, 2016b); and 5) one study evaluated the acute effects of following the PD consumption (Bligh et al, 2015). In addition, one additional study (Mellberg et al, 2014) was added after the manual search of references.…”
Section: Resultsmentioning
confidence: 99%
“…During this time, scientific evidence about the health benefits of ancestral diets has also been accumulating. Benefits for treatment of type-2 diabetes [3], [4], [5], [6], [7], [8], cardiovascular disease [4], [9], [10], [11], multiple sclerosis [12], [13], inflammatory bowel disease [14], obesity [15], and all-cause mortality [16] have been documented through human trials.…”
Section: Scientific Evidencementioning
confidence: 99%